Stevenmentor.com : created by internationals for internationals - Thompson, Kenneth R., (SAGE business cases, 2021)
Samuel Padilla Castro wanted to follow his father's entrepreneurial path and create a business that would help society. Samuel was recruited for his skill in tennis to the Morningside College in Sioux City, Iowa. With the help of Morningside's entrepreneur program and Samuel's own efforts, he developed a web platform, Stevenmentor.com, which he coined as an organization, "created by internationals for internationals." Samuel worked hard to face the early challenges of how to start his own business, complying with student visa regulations, creating a product with limited resources, including networking with other students to find needed skills sources, and working to promote his product to other collegiate and foreign student assistance organizations to build his product base. Samuel has completed the incubator phase and is now looking for ways to accelerate growth for his product.